Evolution and Early Government Responses to Covid-19 in South America - Gonzalez-Bustamante, B (Elsevier Ltd, 2021)
This article analyses the evolution of COVID-19 and early government responses to the pandemic in eight South American countries. To this aim, this study explores indicators which trace the progression of the pandemic and analyses factors related of state capacity which impacted on the early response of governments of implementing restrictive policies of social distancing associated with a suppression strategy. The pressure on the health systems is evaluated with early projections of the growth-phase of the epidemic, which is incorporated as an indicator in the analysis of early interventions based on Cox proportional hazards models. The results indicate that fiscal expenditure on health, regional and local government capacity, and pressure on the health system accelerate government response with stringent interventions. A counter-intuitive finding is that the economic strength of a country delays these types of reactions. The effect of these interventions is something that should be studied in greater depth, considering, for example, sociocultural factors. Lastly, only cases such as Uruguay and Paraguay show some signs of having the pandemic relatively under control by mid-May, while Brazil and Peru face very adverse scenarios. In this context, considering the characteristics of the states in the region and the level of informal employment, it will be a public policy challenge to keep the equilibrium between restrictive measures and the economic and social problems which these responses imply in the medium term. © 2020 Elsevier Ltd